Quantitative estimation of Nipah virus replication kinetics in vitro - Chang, L.Y.; Ali, A.R.M.; Hassan, S.S.; AbuBakar, Sazaly (2006)
Background: Nipah virus is a zoonotic virus isolated from an outbreak in Malaysia in 1998. The virus causes infections in humans, pigs, and several other domestic animals. It has also been isolated from fruit bats. The pathogenesis of Nipah virus infection is still not well described. In the present study, Nipah virus replication kinetics were estimated from infection of African green monkey kidney cells (Vero) using the one-step SYBR (R) Green I-based quantitative real-time reverse transcriptase-polymerase chain reaction (qRT-PCR) assay. Results: The qRT-PCR had a dynamic range of at least seven orders of magnitude and can detect Nipah virus from as low as one PFU/mu L. Following initiation of infection, it was estimated that Nipah virus RNA doubles at every similar to 40 minutes and attained peak intracellular virus RNA level of similar to 8.4 log PFU/mu L at about 32 hours post-infection (PI). Significant extracellular Nipah virus RNA release occurred only after 8 hours PI and the level peaked at similar to 7.9 log PFU/mu L at 64 hours PI. The estimated rate of Nipah virus RNA released into the cell culture medium was similar to 0.07 log PFU/mu L per hour and less than 10 of the released Nipah virus RNA was infectious. Conclusion: The SYBR (R) Green I-based qRT-PCR assay enabled quantitative assessment of Nipah virus RNA synthesis in Vero cells. A low rate of Nipah virus extracellular RNA release and low infectious virus yield together with extensive syncytial formation during the infection support a cell-to-cell spread mechanism for Nipah virus infection.